2017
DOI: 10.1371/journal.pone.0182172
|View full text |Cite
|
Sign up to set email alerts
|

Objective quantification of the food proximity effect on grapes, chocolate and cracker consumption in a Swedish high school. A temporal analysis

Abstract: Close food proximity leads to increased short-term energy intake, potentially contributing to the long-term development of obesity. However, its precise effects on eating behaviour are still unclear, especially with food available for extended periods of time. This study involved two similar high school student groups (15–17 years old), which had ad libitum access to grapes, chocolates and crackers during an hour-long experimental session. In the distal condition the foods were placed 6 meters away from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Chocolate pieces of Galaxy Minstrels were chosen as the unhealthy option as research indicates that individuals snack on chocolate more when compared to crisps and biscuits (Wallis & Hetherington, 2009). Whilst grapes do contain high levels of natural sugars, compared to chocolates grapes contain less fat and more protein and are consequently considered to be more "healthy" than chocolates (Langlet, Fagerberg, Glossner, & Ioakimidis, 2017;Zellner et al, 2006). Both grapes and chocolates were chosen due to them being "sweet" foods, with research indicating that students consume more sweet foods when stressed, in comparison to other food types (Emond et al, 2016;Kim, Yang, Kim, & Lim, 2013 116 health psychology report…”
Section: Methodsmentioning
confidence: 99%
“…Chocolate pieces of Galaxy Minstrels were chosen as the unhealthy option as research indicates that individuals snack on chocolate more when compared to crisps and biscuits (Wallis & Hetherington, 2009). Whilst grapes do contain high levels of natural sugars, compared to chocolates grapes contain less fat and more protein and are consequently considered to be more "healthy" than chocolates (Langlet, Fagerberg, Glossner, & Ioakimidis, 2017;Zellner et al, 2006). Both grapes and chocolates were chosen due to them being "sweet" foods, with research indicating that students consume more sweet foods when stressed, in comparison to other food types (Emond et al, 2016;Kim, Yang, Kim, & Lim, 2013 116 health psychology report…”
Section: Methodsmentioning
confidence: 99%
“…Efforts to use off-the-shelf wearable technologies (e.g., smartwatches) for meal analyses are promising [35], but they are currently not widely available for large-scale use. Thus, the predominant methodology for objective, non-invasive behavioral analysis of meals is the use of video observation, especially for studies performed in controlled [16] and semi-controlled settings [36]. Further, video meal analysis is usually the "ground truth" for the development of other objective analysis methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…On an individual level, the large difference in confidence interval ranges across individuals of both food intake weight and eating rate, suggests measuring manipulation/treatment response in real-life requires more measurements in certain individuals. It has been previously reported that meal-specific food intake is affected by different environmental parameters, just like food proximity [31] and accessibility [32], social environment [33]. In other cases, restricted time during the meal [34] has been shown to affect both eating rate and food intake weight in semi-controlled meals.…”
Section: Discussionmentioning
confidence: 99%